Two Better Than One? Potential Effects of Intraguild Predation on the Biological Control of Ceratitis capitata (Diptera: Tephritidae) by the Parasitoid Aganaspis daci (Hymenoptera: Figitidae) and the Predator Pseudoophonus rufipes (Coleoptera: Carabidae) - De-Pedro, Luis; Beitia, Francisco J.; Tormos, José (MDPI, 2023)
The use of more than one species to manage a single insect pest is a common practice among biological control programs. However, the beneficial effects of natural enemies are not always additive, which in many cases may be attributed to interspecific interactions such as intraguild predation (IGP). Herein, we investigated the potential IGP between two relevant natural enemies of the Medfly (Ceratitis capitata), the predator Pseudoophonus rufipes and the parasitoid Aganaspis daci, as well as the possible implications of this phenomenon in their efficiency as biocontrol agents. To this end, we assessed their functional responses and different demographic parameters when acting alone and together against C. capitata under laboratory conditions. Coexistence led to a switch in the functional response of both species, from type III to type II in A. daci and the opposite in P. rufipes. Regarding demographic parameters, coexistence resulted in higher parasitoidism and population reduction by A. daci only at low host densities, probably due to competition pressure. In the same circumstances, P. rufipes reduced its predatory activity, rejecting those larvae that were presumably parasitized and causing negligible IGP. At high Medfly densities, A. daci efficiency decreased, and the reduced encounter probability enhanced the predatory activity by P. rufipes. As a result of these trends, Medfly population reduction reached almost 100% at all densities, which suggests an additive effect of both natural enemies and recommends combined releases of these agents as a strategy for the control of the Medfly.